Therapeutic Properties of Kuchala – A Short Review - Mudhgi, Priya; Tomar, Brijendra Singh; Chawla, Satbir Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Medicinal plants are a pool of organically active compounds. In texts, there are various allusions to the use of vishdraya as a medicine. Kuchala (Strychnos nux-vomica Linn), an evergreen tree, commonly known as poison nut is attributed with both poisonous and medicinal values. Alkaloids are the main bioactive ingredients in S. nux-vomica Linn, 80% of which are strychnine and brucine, as well as their derivatives such as brucine N-oxide or isostrychnine. In Ayurveda, it has been used for curing various ailments including paralysis, dyspepsia, itching, joint pain, dysentery, emotional disorders, epilepsy, insomnia, etc. after proper shodhana process. Different studies reported safety and toxicity aspects while other studies reported antimicrobial, antidiabetic, hepatoprotective, immunomodulatory, antipyretic, etc. activities of the plant. In this review, an attempt has been made to understand its therapeutic potential by assimilating traditional medicinal knowledge and modern scientific findings about nux vomica. Strychnos nux-vomica Linn (Family: Loganiaceae), a medicinally important toxic plant, commonly known as nux vomica, poison nut, has manifold therapeutic and clinical implementation. This plant is commercially cultivated in different parts of the world such as the United States, the European Union, Fujian, Guangdong, Guangxi, Hainan, North Australia, Taiwan, and throughout tropical Asia.[1] Different parts of this plant, especially seeds and bark, own an ample variety of indications in long-established traditional and folklore medicines of different countries. At present, nux vomica is utilized in more than 60 formulations of Indian systems of medicine of which 30 formulations are used in the disorders of vata dosha.[2] The indole alkaloids, strychnine, and brucine, are richly present in different parts of this plant. These alkaloids pose a wide range of therapeutic potential. It is used as an appetite suppressant, purgative, and as a constituent of nerve toxin along with its uses as rodenticide, respiratory stimulants, and killing stray dogs.[1]